PENGEMBANGAN MODEL BISNIS KONVERSI SEPEDA MOTOR LISTRIK DI INDONESIA (STUDI KASUS PT. EKOLEKTRIK KONVERSI MANDIRI) - Aqil, Hilmy; Sutopo, Wahyudi; Rochani, Renny (Jurnal Ilmiah Teknik Industri, 2024)
The electric motorcycle conversion program is an initiative introduced by the Indonesian government aimed at reducing dependence on fossil fuels and lowering greenhouse gas emissions. This research aims to develop an effective business model for PT. Ekolektrik Konversi Mandiri in converting gasoline-powered motorcycles into electric motorcycles. The research methodology uses a descriptive qualitative approach, including case study analysis, interviews with stakeholders, and evaluation of various relevant business models. The results show that a business model prioritizing strategic partnerships, operational efficiency, and a strong value proposition for consumers can enhance the success and sustainability of the electric motorcycle conversion business. Additionally, the research identifies key challenges such as high conversion costs and limited supporting infrastructure and provides recommendations to address these barriers. With the right business model, electric motorcycle conversion businesses like PT. Ekolektrik Konversi Mandiri are expected to significantly contribute to the Indonesian government's target of achieving Net Zero Emissions by 2060.